Knowledge, Preparedness, and Practices of Lanna People for Earthquake-Resistant Housing in Active Fault Zones of Northern Thailand - Suchat Tachaudomdach; Tanat Kaochim; Kanisorn Sinthuboon (Journal of Research in Social Science and Humanities, 2025)
An earthquake shakes the earth’s surface, causing structural damage to buildings, houses, bridges, and highways. Analyzing the earthquake resistance of buildings and Lanna traditional houses in Northern Thailand's active fault zones can mitigate these consequences. This study aimed to: 1) assess the earthquake resistance of buildings and Lanna traditional houses in these zones, and 2) examine the knowledge, preparedness, and practices of Lanna people regarding earthquake-resistant housing. The results revealed that 1.80% of buildings and Lanna traditional houses were not strong enough to withstand earthquakes. However, Lanna people in active fault zones demonstrated a high level of knowledge, preparedness, and practice in earthquake-resistant housing. Lanna traditional houses often use locally available materials like wood, leaves, stone, and bamboo, which are flexible and resilient during earthquakes. These materials are more sustainable than modern construction materials due to their lower environmental impact and cost-effectiveness. Engineers play a crucial role in ensuring homes are earthquake-resistant while preserving the cultural and historical essence of Lanna Thai architecture. By integrating modern engineering practices with traditional design elements, they create homes that are both safe and culturally significant.